ICT Equipment Maintenance System for IPK Selangor - THAMILSELLVAN A/L PAMANATHE, THAMILSELLVAN A/L PAMANATHE; PROF. Dr. ABD SAMAD BIN HASAN BASARI, PROF. Dr. ABD SAMAD BIN HASAN BASARI (Applied Information Technology And Computer Science, 2025)
The ICT Equipment Maintenance System for IPK Selangor is a web-based information system developed to improve the management and maintenance of ICT equipment in Selangor’s police departments, including IPK, IPD, and Balai Polis. The current manual system, depend on Microsoft Excel and traditional communication methods via phone calls or letters, suffers from inefficiencies such as limited data accessibility, manual data entry errors, and delays in repair status updates, which impact operational performance. This project aims to design, develop, and test a structured system with modules like user management, real-time data entry, status tracking, automated notifications, report genaration and manage logs. The agile methodology guided the systematic development process. The system is expected to enhance communication, streamline workflows, reduce errors, and improve resource allocation and decision-making. By centralizing ICT maintenance processes, the system will improve operational efficiency and ensure quick repairs.